VERBAL AND VISUAL REPRESENTATION OF WOMEN IN ADVERTISEMENTS:A CRITICAL ANALYSIS OF NIKE PRINT COMMERCIALS - Yessy Zakaria, - (2009)
This paper entitled Verbal and Visual Representation of Women in Advertisements: A Critical Analysis of Nike Print Commercials is aimed at examining the verbal and visual representation of women in Nike print advertisements and the ideologies behind the representation. The present study is largely qualitative using the frameworks of Critical Discourse Analysis proposed by Fairclough (2003) and Visual theory of mood and modality by Gunther and Van Leeuwen (1990). Data include six Nike print advertisements that were released in June 2007 until April 2009. The analysis of verbal texts focuses on transitivity, inclusion and exclusion of elements of social events, and concreteness or abstraction of representation of social events. Meanwhile, mood, subjectivity, social distance, and modality analyses are employed in exploring the visual texts. This study reveals that Nike print advertisements portray women as active and prominent subjects. The analyses also show that the ideology underlying the representation appears to be male-oriented emancipation.